Anti-Inflammatory Effect of Aqueous Leaf Extract of Nyctanthes Arbor-Tristis (Alena) on Wistar Rats - Suresh, T.S.; Ifham, I. (Proceedings of 3rd Annual Scientific Conference of Sri Lanka Association for Laboratory Animal Science, 28th & 29th January 2016, University of Sri Jayewardenepura, 2016)
Attached

Introduction and Objectives: Nictanthes arbor-tristis Linn is one of the most useful traditional medicinal plants in India. It is distributed widely in sub Himalayan regions and Southward to Godavari. Each part of the plant has some medicinal value. The objective of this study was to determine the anti-inflammatory activity of aqueous leaf extract of Nyctanthes arbor-tristis (ALENA) in Wistar rats. Methodology: Ethics Review Committee of the Faculty of Medical Sciences, University of Sri Jayewardenepura approved the protocol (Approval No - 682/12). Animals were used in the experiments adhering to the 3R principle. The extract was prepared according to the traditional Ayurveda method as previously described (Hemachandra and Suresh, 2008) and tested for anti-inflammatory activity in a carrageenan induced paw-oedema model. The reductions of paw oedema in rats were compared with the reference drug i.e. Indomethacin. Group 1(6 per group) was pretreated with distilled water at a dose of 5 ml/kg, Group 2 was pretreated with Indomethacin at a dose of 10 mg/kg and the Group 3 was pretreated with aqueous leaf extract of Nyctanthes arbor-tristis, at a dose of 5 ml/kg (Hemachandra and Suresh, 2008), 1 hour prior to the administration of carrageenan. Paw volumes were measured hourly for 5 consecutive hours in carrageenan induced paw oedema models. Several biochemical parameters were tested following admis arbor-tristis Linn, did not exert any adverse effects as all the tested parameters (liver enzymes and Hb) were not altered in the test and control groups. Conclusion: The aqueous leaf extract of Nyctanthes arbor-tristis has potent antiinflammatory effect in Wistar rats.
Keywords: Nyctanthes arbor-tristis Linn.; anti-inflammatory activity; Wistar rats